2022
DOI: 10.52380/ijpes.2022.9.3.1080
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in Teaching and Job Burnout: The Mediating Role of Self-Efficacy

Abstract: Job burnout is a problem characterized by physical and mental problems caused by intense working conditions. In recent years, many teachers on a global scale have stated that they have experienced job burnout. It is known that many teachers who experience job burnout report sleep, fatigue, desire to quit work, low level of professional satisfaction and wellbeing. Although it is known that there are negative relationships between mindfulness, self-efficacy in classroom management, and job burnout, no research h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Nurcahyani et al (2022) found that self-efficacy mediated the relationship between teaching practice experience and interest in becoming a teacher. Another study conducted by Gördesli (2022) H7. Self-efficacy acts as a mediator between supervisor support and job performance.…”
Section: H4 Work Engagement Improves Job Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Nurcahyani et al (2022) found that self-efficacy mediated the relationship between teaching practice experience and interest in becoming a teacher. Another study conducted by Gördesli (2022) H7. Self-efficacy acts as a mediator between supervisor support and job performance.…”
Section: H4 Work Engagement Improves Job Performancementioning
confidence: 99%
“…Nurcahyani et al (2022) found that self‐efficacy mediated the relationship between teaching practice experience and interest in becoming a teacher. Another study conducted by Gördesli (2022) investigated that mindfulness in teaching and job burnout is partially mediated by self‐efficacy. Hussain et al (2021) collected responses through a social networking website and found that full mediation exists between the use of social networking sites and green entrepreneurship intentions.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%